EFEKTIVITAS META BUSINESS SUITE DALAM MANAJEMEN KONTEN MEDIA SOSIAL EDUKASI ANAK: STUDI KASUS PT NARUNA KARYA BERSAMA - Syahputra, Irfan Arya; Aminah, Siti (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This research examines the effectiveness of using Meta Business Suite in enhancing social media content management for children’s education, with a case study on PT Naruna. The study analyzes the impact of implementing Meta Business Suite on content management efficiency, audience engagement, and achievement of educational goals. The research methodology involves analyzing quantitative data from social media metrics and conducting qualitative interviews with PT Naruna’s content management team. Results show significant improvements in team productivity, posting consistency, and interaction with the target audience. These findings provide valuable insights into the potential of Meta Business Suite for optimizing social media strategies in children’s educational content, as well as its implications for similar companies in the education industry.